Concept mapping improves academic performance in problem solving questions in biochemistry subject - Baig, Mukhtiar; Tariq, Saba; Rehman, Rehana; Ali, Sobia; Gazzaz, Zohair J (Pakistan journal of medical sciences, 2016)
To assess the effectiveness of concept mapping (CM) on the academic performance of medical students' in problem-solving as well as in declarative knowledge questions and their perception regarding CM. The present analytical and questionnaire-based study was carried out at Bahria University Medical and Dental College (BUMDC), Karachi, Pakistan. In this analytical study, students were assessed with problem-solving questions (A-type MCQs), and declarative knowledge questions (short essay questions), and 50% of the questions were from the topics learned by CM. Students also filled a 10-item, 3-point Likert scale questionnaire about their perception regarding the effectiveness of the CM approach, and two open-ended questions were also asked. There was a significant difference in the marks obtained in those problem-solving questions, which were learned by CM as compared to those topics which were taught by the traditional lectures (p<0.001), while no significant difference was observed in marks in declarative knowledge questions (p=0.704). Analysis of students' perception regarding CM showed that majority of the students perceive that CM is a helpful technique and it is enjoyed by the students. In open-ended questions, the majority of the students commented positively about the effectiveness of CM. Our results indicate that CM improves academic performance in problem solving but not in declarative knowledge questions. Students' perception about the effectiveness of CM was overwhelmingly positive.